1996
DOI: 10.1111/j.1440-1819.1996.tb02747.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐existence of a positive correlation between urinary levels of α1 ‐microglobulin and ulinastatin in patients with Parkinson's disease

Abstract: Urinary levels of alpha 1-microglobulin (alpha 1M) and of ulinastatin (UT) and the alpha 1M/UT ratio did not differ significantly between age-matched controls and patients with Parkinson's disease, and among subdivided groups based on Yahr's stages in Parkinson's disease. Furthermore, these indexes did not correlate with Yahr's stages. Although alpha 1M and UT levels did not correlate in patients with Parkinson's disease, a positive correlation was observed in the control group. The non-existence of a positive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…administered IL-1ß or IL-6. As a result, we found that the lack of correlation between urinary contents of ·1M and UT, a phenomenon observed in patients with Parkinson's disease [7], was reversibly induced by IL-6, but not IL-1ß.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…administered IL-1ß or IL-6. As a result, we found that the lack of correlation between urinary contents of ·1M and UT, a phenomenon observed in patients with Parkinson's disease [7], was reversibly induced by IL-6, but not IL-1ß.…”
Section: Introductionmentioning
confidence: 67%
“…In our previous study, we have found that the lack of a positive correlation between urinary contents of ·1M and UT distinguishes Parkinson's disease from other neuropsychiatric diseases such as dementia (Alzheimer-type and vascular dementia), schizophrenia and mood disorder [7], although the mechanism(s) remains to be elucidated. This lack of ·1M/UT correlation can be reproducibly induced by treatment with either 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP; a compound which produces pathological changes similar to those observed in idiopathic Parkinson's disease in humans) or 1-methyl-4-phenylpyridinium (MPP + ; a neurotoxic metabolite of MPTP) in mice [22,23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nulliÞcation of this correlation was observed in patients with Parkinsons disease (Inagaki et al 1996b) and MPTPtreated mice (repetitively administered IP) (Shikimi et al 1997). In the present study, nulliÞcation of the positive correlation between urinary contents of a 1 M and UT was also observed after ICV administration of either MPTP or MPP + .…”
Section: Discussionmentioning
confidence: 96%
“…However, mutual and physiologically relevant functions in vivo are still obscure. In the course of our studies on the relationship between renal function and the urinary content of ·1M and UT, we have found that the relationship between the urinary content of ·1M and UT varies with the type of psychoneurotic disease in patients without renal/hepatic dysfunction [4][5][6]. In these studies, the slope of the regression line relating the urinary content of ·1M and UT is steeper in patients with mood disorders (MD) than in age-matched healthy subjects [5].…”
Section: Introductionmentioning
confidence: 82%